The Psychological Character of Rosemary Fell in Katherine Mansfield’s Short Story Entitled "A Cup of Tea" - Ratna Asmarani (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
The purpose of this paper is to analyze the psychological character of the upper class woman in Katherine Mansfield’s short story entitled A Cup of Tea. The analysis is based on the concept of narcissism, Maslow’s concept of esteem needs, and consumerism. The method of literary analysis is a contextual one focusing on the intrinsic and extrinsic elements. The result shows that the female character has a low self-esteem with narcissistic grandiosity. Such psychological character always needs attention, appreciation, and praises from other people that are obtained by following upper class exclusive and consumptive way of life. It can be concluded that a narcissistic upper class female often hides vulnerable self-esteem by camouflaging it with glamorous appearance full of self-confidence.Keywords: narcissism, esteem needs, consumerism, upper class